Risks associated with discontinuation of oral anticoagulation in newly diagnosed patients with atrial fibrillation: Results from the GARFIELD‐AF Registry. (23rd July 2021) - Cools, Frank; Johnson, Dana; Camm, Alan J.; Bassand, Jean‐Pierre; Verheugt, Freek W. A.; Yang, Shu; Tsiatis, Anastasios; Fitzmaurice, David A.; Goldhaber, Samuel Z.; Kayani, Gloria; Goto, Shinya; Haas, Sylvia; et al.
Abstract: Background: Oral anticoagulation (OAC) in atrial fibrillation (AF) reduces the risk of stroke/systemic embolism (SE). The impact of OAC discontinuation is less well documented. Objective: Investigate outcomes of patients prospectively enrolled in the Global Anticoagulant Registry in the Field‐Atrial Fibrillation study who discontinued OAC. Methods: Oral anticoagulation discontinuation was defined as cessation of treatment for ≥7 consecutive days. Adjusted outcome risks were assessed in 23 882 patients with 511 days of median follow‐up after discontinuation. Results: Patients who discontinued ( n  = 3114, 13.0%) had a higher risk (hazard ratio [95% CI]) of all‐cause death (1.62 [1.25–2.09]), stroke/systemic embolism (SE) (2.21 [1.42–3.44]) and myocardial infarction (MI) (1.85 [1.09–3.13]) than patients who did not, whether OAC was restarted or not. This higher risk of outcomes after discontinuation was similar for patients treated with vitamin K antagonists (VKAs) and direct oral anticoagulants (DOACs) ( p for interactions range = 0.145–0.778). Bleeding history (1.43 [1.14–1.80]), paroxysmal vs. persistent AF (1.15 [1.02–1.29]), emergency room care setting vs. office (1.37 [1.18–1.59]), major, clinically relevant nonmajor, and minor bleeding (10.02 [7.19–13.98], 2.70 [2.24–3.25] and 1.90 [1.61–2.23]), stroke/SE (4.09 [2.55–6.56]), MI (2.74 [1.69–4.43]), and left atrial appendage procedures (4.99 [1.82–13.70]) were predictors of discontinuation. Age (0.84 [0.81–0.88], per 10‐year increase), history of stroke/transient ischemic attack (0.81 [0.71–0.93]), diabetes (0.88 [0.80–0.97]), weeks from AF onset to treatment (0.96 [0.93–0.99] per week), and permanent vs. persistent AF (0.73 [0.63–0.86]) were predictors of lower discontinuation rates. Conclusions: In GARFIELD‐AF, the rate of discontinuation was 13.0%. Discontinuation for ≥7 consecutive days was associated with significantly higher all‐cause mortality, stroke/SE, and MI risk. Caution should be exerted when considering any OAC discontinuation beyond 7 days.